Teaching probabilistic medical reasoning with the Elvira software - Díez, F.J. (Yearbook of Medical Informatics, 2004)
This paper briefly describes the main features of the UNED (Spanish National University for Distance Education) and the course on Probability and Statistics in Medicine. Then it introduces Bayesian networks and influence diagrams, two of the methods taught in this course. Finally, it explains how Elvira, a software package, can help the students to understand some difficult probabilistic concepts.